Effect of thermal stress and water restriction on cortisol level of Beetal and Black Bengal goats - KAUSHISH, S K; SENGUPTA, B P; GEORGIE, G C (The Indian Journal of Animal Sciences, 2013)
The study was conducted on 5-6-month-old male kids (9 Beetal and 9 Black Bengal). Six kids from each breed were divided into 2 groups. In 1 group water was not withheld. whereas in the other it was withheld for 36 hr before exposure to thermal stress (43.5+-0.5 Â°C. RH 55%). The observations were recorded before exposure and then at Vz hr interva,ls during 2 hr exposure. Cortisol concentration in control. thermal stress and thermal stress coupled with water stress groups were 17.6+-2.68,54.3+-1.71 and 38.5+-5.13 ng/ml in Beetal and 48.1+-3.60, 43.7+-5.32 and 55.5+-5.72 nglml in Black Bengal goats. respectively. Significant increase in cortisol level was observed in Beetal on exposure to thermal stress. but the increase was nonsigrliticant in Black Bengal. It is concluded that Black Bengal were more adapted to hot humid conditions than Beetal.